Benedykt Bornstein’s reception of Immanuel Kant’s philosophy - Śleziński, Krzysztof (Folia Philosophica, 2017)
Benedykt Bornstein belongs to a group of philosophers, who demonstrated an opportunity for development of the scientific metaphysics with the use of the axiomatic method. His general theory of existence was developed under the influence of critical discussion on the major problems related to Kant’s theory of cognition. Arguments presented in this article are to be an attempt to recognise all the assumptions and conditions which our philosopher investigated. It is stressed that in the context of native philosophy Bornstein is neo-kantian as well as a representative of Polish analytical philosophy. However, his epistemological and ontological analyses have not met the proper reception by the environment of Lvov-Warsaw School. Although, he has remained Kazimierz Twardowski’s student in terms of character of his methodological research, strive for terminological precision and the use of formal language in his arguments.